Seedball‐induced changes of root growth and physico‐chemical properties—a case study with pearl millet. Issue 5 (20th August 2018) - Nwankwo, Charles I.; Blaser, Sebastian R. G. A.; Vetterlein, Doris; Neumann, Günter; Herrmann, Ludger
Abstract: Seedball is a cheap "seed‐pelleting‐technique" that combines local materials, seeds and optionally additives such as mineral fertilizer to enhance pearl millet ( Pennisetum glaucum (L.) R. Brown) early growth under poor soil conditions. The major objective here was to study the mechanisms behind positive seedball effects. Chemical effects in the rhizosphere and early root development of seedball‐derived pearl millet seedlings were monitored using micro‐suction‐cups to extract soil solutions and X‐ray tomography to visualize early root growth. Pearl millet (single seedling) was grown in soil columns in a sandy soil substrate. Root and shoot biomass were sampled. X‐ray tomography imaging revealed intense development of fine roots within the nutrient‐amended seedball. Seedball and seedball+NPK treatments, respectively, were 65% and 165% higher in shoot fresh weight, and 108% and 227% higher in shoot dry matter than the control treatment. Seedball+NPK seedlings showed promoted root growth in the upper compartment and 105% and 30% increments in root fresh and dry weights. Soil solution concentrations indicate that fine root growth ass stimulated by release of nutrients from the seedballs to their direct proximity. Under real field conditions, the higher root length density and finer roots could improve seedlings survival under early drought conditions due to better ability to extract water and nutrients from a greater soil volume.